Psychiatric symptoms in children with COVID-19, mothers` psychological resilience and related factors: pandemic hospital inpatient experiences - Çöp, Esra; Akçay, Elif; Dinç, Gülser Şenses; Göker, Zeynep; Önal, Tuğçe; Gülhan, Belgin; Parlakay, Aslınur; Üneri, Özden Şükran (The Turkish Journal of Pediatrics, 2022)
Background. Information on psychological problems and affecting factors in children hospitalized with the suspicion or diagnosis of COVID-19 is limited. We aimed to screen the psychiatric symptoms of children hospitalized with COVID-19 in Ankara City Children`s Hospital and evaluate the caregivers` depression, anxiety, stress, and resilience levels during hospitalization. Methods. Among the children and adolescents hospitalized in Ankara City Children`s Hospital between 1 May 2020 and 31 May 2020 due to the diagnosis of COVID-19, those who agreed to participate in the study were included. The Strengths and Difficulties Questionnaire (SDQ), the Depression Anxiety Stress Scale-21 (DASS- 21) scale, and the Brief Resilience Scale (BRS) were used to determine the symptoms. Results. The mean age of study group (n = 49) was 8.7 ± 5.0 years, 59.2% (n = 29) were girls. The mean children`s SDQ-externalizing problems scores were higher in the COVID-19 positive mothers group than the COVID-19 negative mothers` group. The SDQ-total score was positively and strongly correlated with the DASS total score, DASS-depression score, and DASS-anxiety score. BRS scale scores were negatively correlated with the SDQtotal, externalizing, and DASS-21scale scores. Conclusions. COVID-19 positivity in mothers could be associated with externalizing problems in children. The high resilience of caregivers of inpatients seems to be related to less psychopathology in children. During hospitalization, caregivers` psychological evaluation and psychosocial support may be important for preventive child mental health.